Framing a human rights approach to communication surveillance laws through the African human rights system in Nigeria, South Africa and Uganda (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
Today, in any society where crime is possible, communication surveillance is a necessary evil. This is because technologies now offer faster means of preventing crime while they are also capable of undermining the right to privacy. However, protecting privacy should not be mutually exclusive of ensuring public safety. This article argues that while communication surveillance may be permissible under narrow and limited circumstances, the laws made to regulate it in Nigeria, South Africa andUganda do not comply with international human rights standards. In demonstrating this, this article analyses the major laws in these countries alongside the various international human rights principles that must be complied with in framing a rights-respecting law on communication surveillance. The major contribution of this article is that communicationsurveillance laws can be designed in compliance with international human rights standards in the countries under focus. These include Nigeria, South Africa and Uganda carrying out specific legal reforms targeted at problematic laws on communication surveillance in order to bring them in line with international human rights standards. This can also be supportedby developing a more robust set of comprehensive guidelines through the African Commission and Human and Peoples’ Rights and ensuring that Nigeria, South Africa and Uganda embark on critical and strategic training for stakeholders involved in the enforcement and implementation of communication surveillance laws in these countries.